North-South and South-South Trade-Related Technology Diffusion: How Important Are They in Improving TFP Growth? - Schiff, Maurice (2012)
This paper examines the impact on total factor productivity (TFP) growth in the South of North-South and South-South trade-related technology diffusion and of foreign direct investment (FDI). North-South and South-South trade-related research and development (R&D) stocks are constructed based on industry-specific R&D in the North, North-South and South-South trade patterns, and input-output relations in the South. The main findings are: 1. both North-South and South-South trade-related R&D have a positive impact on TFP growth in the South; 2. FDI has a positive, though smaller, impact on TFP growth; and 3.the impact on TFP growth of trade-related technology diffusion increases with the level of education in the case of North-South trade but not in the case of South-South trade.